PENGARUH PERAN PENDETA TERHADAP PEMAHAMAN DAN PENERAPAN DOKTRIN BAIT SUCI DI LINGKUNGAN GEREJA MASEHI ADVENT HARI KETUJUH - Elfri Darlin Sinaga (Jurnal Theologia Forum STFT Surya Nusantara, 2018)
The Doctrine of Sanctuary is one of the most important Bible Doctrines within the Seventh-day Adventist Church. The correct understanding about the priesthood ministry of Christ in the Heavenly Sanctuary must be understood and implemented fully by its church’s members. There are assumptions that many of church members have a little understanding about the doctrine of sanctuary and they have a lack understanding about the benefit of that doctrine to be understood and implemented in everyday life. What is the level of understanding of that doctrine within the Seventh-day Adventist church members? How much is the application of Sanctuary Doctrine within the members of the congregation? Then, what is the level of influence of the pastor’s role in teaching that doctrin to his church members? This research aims to enhance the role of the pastor in educating and equipping the church members have a full understanding on theological teachings on sanctuary doctrine and its implementation in everyday life. The result of this study indicated that the level of understanding of the church members on the doctrine of Sanctuary (Y1) was on the score value 2.976 or hesitation and the implementation (Y2) was on the the score value 2.128 or disagree. The influence of the pastor’s role as educator in teaching of sanctuary’s doctrine towards the theological understanding of the Seventh-day Adventists church’s members throughout the municipality Pematangsiantar are at 0,316 or 9.9% and the influence of the pastor’s role towards the implementation of the doctrine of Sanctuary in the life of the church members are at 0.369 or 13.6%. It means that contributions given by the pastor toward the understanding of the church members (Y1) and toward the implementation of the doctrine of sanctuary in the life of the church members (Y2) exists but is weak or insignificant. Based on the results of this research will provide advice to church’s pastor in order to further enhance its role in teaching that doctrine and its implementations, so that all church’s members become more proficient on that subject and should prepare themselves worthy to receive the merit of Christ mediation’s services in the Heavenly Sanctuary.